New land-use-change emissions indicate a declining CO 2 airborne fraction - van Marle, Margreet J.E.; van Wees, Dave; Houghton, Richard A.; Field, Robert D.; Verbesselt, Jan; van der Werf, Guido R. (Nature, 2022)
About half of the anthropogenic CO 2 emissions remain in the atmosphere and half are taken up by the land and ocean 1 . If the carbon uptake by land and ocean sinks becomes less efficient, for example, owing to warming oceans 2 or thawing permafrost 3 , a larger fraction of anthropogenic emissions will remain in the atmosphere, accelerating climate change. Changes in the efficiency of the carbon sinks can be estimated indirectly by analysing trends in the airborne fraction, that is, the ratio between the atmospheric growth rate and anthropogenic emissions of CO 2 (refs. 4–10 ). However, current studies yield conflicting results about trends in the airborne fraction, with emissions related to land use and land cover change (LULCC) contributing the largest source of uncertainty 7,11,12 . Here we construct a LULCC emissions dataset using visibility data in key deforestation zones. These visibility observations are a proxy for fire emissions 13,14 , which are — in turn — related to LULCC 15,16 . Although indirect, this provides a long-term consistent dataset of LULCC emissions, showing that tropical deforestation emissions increased substantially (0.16 Pg C decade −1 ) since the start of CO 2 concentration measurements in 1958. So far, these emissions were thought to be relatively stable, leading to an increasing airborne fraction 4,5 . Our results, however, indicate that the CO 2 airborne fraction has decreased by 0.014 ± 0.010 decade −1 since 1959. This suggests that the combined land–ocean sink has been able to grow at least as fast as anthropogenic emissions.